Upaya Pengembangan Kompetensi Guru Sekolah Dasar Dalam Kurikulum Merdeka Belajar - Gilang Kartika Hanum; Andri Cahyo Purnomo; Desy Apriani; Ita Erliyani (UNIVERSITAS RAHARJA, 2024)
The aim of the research aimed at this research is to clarify efforts to increase teacher capabilities with the title